Identifying key complex relations between education and healthcare in the Netherlands for future pandemic management - Sophie Hadjisotiriou; Jannie Coenen; Etiënne A. J. A. Rouwette; Vittorio Nespeca; Tom H. Oreel; Vincent A. W. J. Marchau; Vítor V. Vasconcelos; Rick Quax; Heiman F. L. Wertheim; Marcel G. M. Olde Rikkert; Hubert P. L. M. Korzilius (Health Research Policy and Systems)
Abstract Background The effects of the coronavirus disease 2019 (COVID-19) pandemic and subsequent policies in the Netherlands extended beyond healthcare, impacting other societal systems such as education. This study aims to conceptualize a coupled education–healthcare system during a pandemic and identify key variables and relations that affect the accessibility of both systems. This is essential to address the interconnected nature of pandemic policymaking and design policies that account for possible unintended consequences that interventions in healthcare may have on education and vice versa. Methods Group model building and in-depth interviews with actors from healthcare and education were used to develop a coupled causal loop diagram of healthcare and education accessibility in the Netherlands during a pandemic. The causal loop diagram is analysed with cross-impact analysis to identify key leverage points, monitoring variables, feedback loops and relations between healthcare and education. Results Six causal relations were identified between healthcare and education, indicating a relevant impact of healthcare on education during pandemics. Cross-impact analysis identified 24 leverage points, of which 10 were in healthcare, 11 in education and 4 in the contextual environment. During the COVID-19 pandemic in the Netherlands, healthcare utilized all these leverage points, education utilized six and two were used not pertaining to healthcare or education but the contextual environment. Leverage points included the availability and wellbeing of personnel, number of patients, progress of pupils/students and resources. Seven monitoring variables included the availability of personnel, resources in education and progress of pupils/students, and were utilized in healthcare and education during the pandemic. Four feedback loops were found, of which three are reinforcing. One large balancing feedback loop is situated between the healthcare and education system, indicating mutual dependency to maintain staff for the accessibility of healthcare and education. Conclusions Group model building, in-depth interviews and cross-impact analysis identified key variables, causal relations and feedback loops illustrating the coupled nature of healthcare and education during pandemics. This highlights the need for integrated policymaking that addresses and considers coupled systems to ensure accessibility to both healthcare and education. The finalized model can serve as a tool to support such integrated policymaking.